2012
DOI: 10.1902/jop.2011.110275
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Volatile Sulfur Compounds and Periodontal Disease Progression in Elderly Non‐Smokers

Abstract: VSC measurements were significantly associated with periodontal disease progression in a non-smoking dentulous elderly population. This suggests that VSC measurements are useful for the diagnosis of periodontal disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…The CH 3 SH and H 2 S gases are the main VSCs in intra-oral halitosis 1 , and their toxicity is associated with the development of periodontal disease 15 , 16 , 29 . Tea tree oil was able to inhibit the growth of P. gingivalis W83 and P. endodontalis , and the production of VSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The CH 3 SH and H 2 S gases are the main VSCs in intra-oral halitosis 1 , and their toxicity is associated with the development of periodontal disease 15 , 16 , 29 . Tea tree oil was able to inhibit the growth of P. gingivalis W83 and P. endodontalis , and the production of VSCs.…”
Section: Discussionmentioning
confidence: 99%
“…A review paper published in 2001, and a number of studies conducted recently, indicated a significant association between periodontal disease and halitosis (Morita and Wang, ; Lee et al , ; Liu et al , ; Quirynen et al , ; Makino et al , ; Apatzidou et al , ), However, some studies have concluded that there is no significant association between the two (Bosy et al , ; Stamou et al , ). In a study conducted by Liu and colleagues, tongue coating was the leading variable that correlated with VSC values in the final logistic regression (Liu et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of MM and H 2 S were also reported in periodontitis patients by Yaegaki & Sanada (1992 a,b). In addition, elevated VSC levels have been linked to progression of periodontitis (Makino et al 2012). …”
Section: Periodontal Conditions and Intra-oral Halitosismentioning
confidence: 99%